Effectiveness of a Group-Based Culturally Tailored Lifestyle Intervention Program on Changes in Risk Factors for Type 2 Diabetes among Asian Indians in the United States - Rupal M. Patel; Ranjita Misra; Sudha Raj; Ashok Balasubramanyam (Journal of Diabetes Research)
This study used an experimental, pretest-posttest control group repeated measures design to evaluate the effectiveness of a community-based culturally appropriate lifestyle intervention program to reduce the risk for type 2 diabetes (T2DM) among Gujarati Asian Indians (AIs) in an urban community in the US. Participants included 70 adult AIs in the greater Houston metropolitan area. The primary outcomes were reduction in weight and hemoglobin A1c (HbA1c) and improvement in physical activity. Participants were screened for risk factors and randomly assigned to a 12-week group-based lifestyle intervention program (n=34) or a control group (n=36) that received standard print material on diabetes prevention. Participants also completed clinical measures and self-reported questionnaires about physical activity, social, and lifestyle habits at 0, 3, and 6 months. No significant baseline differences were noted between groups. While a significant decline in weight and increase in physical activity was observed in all participants, the intervention group lowered their HbA1c (p<0.0005) and waist circumference (p=0.04) significantly as compared to the control group. Findings demonstrated that participation in a culturally tailored, lifestyle intervention program in a community setting can effectively reduce weight, waist circumference, and HbA1c among Gujarati AIs living in the US.